2016
DOI: 10.1002/rnc.3642
|View full text |Cite
|
Sign up to set email alerts
|

Robust consensus control of uncertain multi‐agent systems with input delay: a model reduction method

Abstract: SUMMARYThis paper addresses the robust consensus control design for input-delayed multi-agent systems subject to parametric uncertainties. To deal with the input delay, the Artstein model reduction method is employed by a state transformation. The input-dependent integral term that remains in the transformed system, due to the model uncertainties, is judiciously analysed. By carefully exploring certain features of the Laplacian matrix, sufficient conditions for the global consensus under directed communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…[24] and [26]- [29] as a special case withζ(t) ≡ 1. Furthermore, if d(t) ≡ 0, condition (28) in [24] degenerates to…”
Section: Stability Analysismentioning
confidence: 99%
“…[24] and [26]- [29] as a special case withζ(t) ≡ 1. Furthermore, if d(t) ≡ 0, condition (28) in [24] degenerates to…”
Section: Stability Analysismentioning
confidence: 99%
“…Ren addressed formation control problems by implementing the consensus‐based approach and showed that the above‐mentioned classical methodologies could be unified in the framework of the consensus‐based formation control. Inspired by the development of the consensus theory in the control community, the newly developed consensus‐based formation control strategies were reported in many application fields including mobile robots, intelligent ground vehicles, and unmanned aerial vehicles (see References and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, robust controllers are necessary to compensate for the effects of model uncertainties. Some strategies have been given to deal with uncertainties in multiagent systems, eg, independent of the state uncertainties, known bounded uncertainties, and Lipschitz condition uncertainties . Thus, the state‐dependent uncertainties cannot satisfy these conditions.…”
Section: Introductionmentioning
confidence: 99%